Núcleos criativos : o desafio de desenvolver e viabilizar projetos audiovisuais - Maruyama, Raquel Leiko Machado (2019)
The present work analyzes the development of audiovisual projects in the creative core modality, financed through a public notice of the Audiovisual Sectorial Fund. The objective is to verify if there are substantial differences in the way the creative cores that managed to renew the investiment with the FSA structured themselves internally and in the way they relate to the Market compared to cores that did not obtain the investiment renewal. This assumption was investigated through a qualitative research through in-depth interviews. It was heard cores’ leaders that aimed the viability of at least two fifths of their projects and cores’leaders that did not reach the same success. The results found were analyzed based on concepts such as Intervenor State and Regulatory State by Ana Carla Reis, culture economy by Françoise Benhamou, creative class by Richard Florida, and creative industries ecosystem by Paul Jeffcutt. They point to the fact that there are more similarities than differences between both groups, but it reveals the importance of leader’s and production companies relational capital. The data and information obtained allow a more systematized view of the development phase of films and series and has applicability for professionals who works as producers, creators and scriptwriters, interested in setting up a creative core, to improve their planning and execution strategies to optimize the chances of making their projects viable. In the public sphere, the content of this research also contributes to the process of evaluation and qualification of policies for the audiovisual sector